Preparation and Evaluation of Lipid Emulsion Containing 13 Vitamins for Injection Without Anaphylactoid Reactions - Hui MQ (Dove Medical Press, 2021)
Min-Quan Hui,1,2,* Yan-Ni Mi,1,* Yu-Fan Ma,2 Tao Chen,2 Yong-Xiao Cao1 1Department of Pharmacology, Health Science Center, Xi’an Jiaotong University, Xi’an, People’s Republic of China; 2Xi’an Libang Pharmaceutical, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong-Xiao CaoDepartment of Pharmacology, Health Science Center, Xi’an Jiaotong University, 76 Yanta West Road, Xi’an, 710061, People’s Republic of ChinaTel +86-29-8265-5140Email yxy@xjtu.edu.cnObjective: Multivitamins containing Tween 80 can cause anaphylactoid reactions. The objective of this study was to develop a new lipid emulsion containing 13 fat- and water-soluble vitamins for injection (13V-LE) that were simultaneously dissolved in one bottle and to evaluate the stability of and anaphylactoid reactions to 13V-LE.Methods: Particle size, ζ-potential, and polydispersity of 13V-LE were assayed with a Zetasizer Nano ZS. Entrapment efficiency of 13V-LE was determined with HPLC. Behavior, histamine, and blood pressure of beagle dogs were investigated by observation, fluorospectrophotometry, and sphygmomanometry.Results: The 13V-LE with the smallest particles and highest entrapment efficiency with stable ζ-potential was composed of soybean oil, glycerin (2.25%, w:v), egg lecithin (1.2%, w:v), and purified water. There was no obvious change in characteristics of the 13V-LE samples in terms of appearance, size distribution, ζ-potential, pH value, or concentration over 6 months. In anaphylactoid reactions tests, when being administered with the multivitamin Infuvite Adult containing Tween 80, six beagles showed grade IV symptoms (P< 0.01 vs control), low blood pressure, and high plasma-histamine concentrations (P< 0.05 or P< 0.01). However, there were no significant differences in behavior, blood pressure, or histamine concentration in the dogs before and after administration in the 13V-LE group.Conclusion: The 13V-LE formulation is a suitable intravenous lipid emulsion without anaphylactoid reactions.Keywords: anaphylactoid reaction, multivitamins, lipid emulsion, beagle dog